2021
DOI: 10.1128/spectrum.00708-21
|View full text |Cite
|
Sign up to set email alerts
|

Unique Gut Microbiome in HIV Patients on Antiretroviral Therapy (ART) Suggests Association with Chronic Inflammation

Abstract: Chronic inflammation is a hallmark of HIV infection and is associated with the development and progression of age-related comorbidities. Although the gastrointestinal tract is a major site of HIV replication and CD4 + T-cell depletion, the role of HIV-associated imbalance of gut microbiome in chronic inflammation is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 47 publications
3
64
0
Order By: Relevance
“…All the patients enrolled in this study were infected with the original SARS-COV-2 strains (Wuhan and Wuhan/D614G strains). A non-COVID-19 control cohort of 40 healthy adults was recruited at the University of Tokyo in 2017 before the COVID-19 pandemic ( 13 ). The non-COVID-19 cohort consisted of 40 male individuals with a median age of 42 years (range, 23–60 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the patients enrolled in this study were infected with the original SARS-COV-2 strains (Wuhan and Wuhan/D614G strains). A non-COVID-19 control cohort of 40 healthy adults was recruited at the University of Tokyo in 2017 before the COVID-19 pandemic ( 13 ). The non-COVID-19 cohort consisted of 40 male individuals with a median age of 42 years (range, 23–60 years).…”
Section: Resultsmentioning
confidence: 99%
“…As a control group, historical cohort data of 40 healthy individuals who were recruited in a previous study ( 13 ) were used. Those who consumed antibiotics within the previous 2 weeks were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbial translocation resulting from dysbiosis and gut damage plays a prominent role in maintaining a persistent underlying chronic inflammatory state in PLWH, and compliant, long-term ART does not entirely reverse damage to the intestinal tract barrier (81,90,(114)(115)(116)(117). Thus the gut fails to successfully repair in PLWH receiving ART (90,114,115).…”
Section: Hiv Infection Is Associated With Gut Microbiome Dysbiosis and Related Inflammationmentioning
confidence: 99%
“…On the other hand, it has become clear that HIV-positive individuals have an unique gut microbiome profile. In our 16S rRNA metagenomic analysis of HIV patients with MSM, we observed that despite long-term viral suppression, the gut microbiome of HIV-infected patients is more aerobic than healthy individuals [ 20 ]. The altered gut microbiome in patients with HIV is considered to be influenced by the HIV infection itself, as well as the antiretroviral therapy (ART) regimen [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%